2022
DOI: 10.1007/s12053-022-10046-9
|View full text |Cite
|
Sign up to set email alerts
|

Profitability comparison of active and passive energy efficiency improvements in public buildings

Abstract: Buildings and construction are responsible for about 40% of the energy and process-related CO2 emissions worldwide. At present, the renewal rate of building stock is relatively low, for example in Finland, which is the case under study in this work, it is 1.5% per year. With respect to the target of a carbon neutral world by 2050, the effect on emissions of existing building stock must be considered. In this paper, we present the results of analysis of energy efficiency improvement investment in 12 city-owned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…• Energy Efficiency Improvements: Enhance the energy efficiency of buildings through better insulation [89,90] , high-efficiency lighting, appliances, and Heating, Ventilation, and Air Conditioning (HVAC) systems [91] to reduce energy consumption and emissions [92,93] .…”
Section: Mitigation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…• Energy Efficiency Improvements: Enhance the energy efficiency of buildings through better insulation [89,90] , high-efficiency lighting, appliances, and Heating, Ventilation, and Air Conditioning (HVAC) systems [91] to reduce energy consumption and emissions [92,93] .…”
Section: Mitigation Strategiesmentioning
confidence: 99%
“…• Promoting Energy Efficiency: Governments can incentivize energy-efficient building designs and retrofits by offering tax incentives, grants, or subsidies. Encouraging the use of renewable energy sources can also reduce energy demand and greenhouse gas emissions [92,93] .…”
mentioning
confidence: 99%
“…Typical energy-saving technologies have been integrated into urban regeneration practices with other urban elements, including retrofitting solar energy and water storage, adding insulation to building envelopes, fitting energy-efficient electric appliances, recycling waste and using eco-friendly materials, etc. [47,48]. For instance, Hashempour et al [37] identified obstacles to promoting the replacement of low-carbon technologies in space heating based on regeneration cases in the Netherlands.…”
Section: Paper Title Authors Citationsmentioning
confidence: 99%
“…Furthermore, urban regeneration strategies to mitigate climate change in different countries show significant geographical features. It is typical that in countries at high latitudes, such as Finland, there is a greater research interest in heating retrofits in urban regeneration projects to reduce energy consumption and associated carbon emissions [48].…”
Section: Research Trend and Agendamentioning
confidence: 99%